2011
DOI: 10.1111/j.1464-5491.2011.03255.x
|View full text |Cite|
|
Sign up to set email alerts
|

The humoral immune response to the inactivated influenza A (H1N1) 2009 monovalent vaccine in patients with Type 2 diabetes mellitus in Korea

Abstract: Our data show low cross-reactive antibody carrying rate and low seroconversion rate in patients with diabetes. Until larger-scale, case-controlled trials become available, older patients and patients with a longer duration of diabetes should be considered for the two-dose vaccination or have antibody titres measured after the first vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
17
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 7 publications
3
17
2
Order By: Relevance
“…23 A third study showed that diabetic patients in the older age range or with longer disease duration showed a lower sero-conversion proportion with A(H1N1)pdm09 vaccine. 24 Such results are broadly consistent with our findings that immunity was sufficient as a whole, but older age, decreased BMI and increased HbA1c level were associated with poor immunogenicity. The reason for these minor differences is unclear, but differences in the severities of DM and the comorbidities or genetic characteristics of the population may have been involved.…”
Section: Discussionsupporting
confidence: 82%
“…23 A third study showed that diabetic patients in the older age range or with longer disease duration showed a lower sero-conversion proportion with A(H1N1)pdm09 vaccine. 24 Such results are broadly consistent with our findings that immunity was sufficient as a whole, but older age, decreased BMI and increased HbA1c level were associated with poor immunogenicity. The reason for these minor differences is unclear, but differences in the severities of DM and the comorbidities or genetic characteristics of the population may have been involved.…”
Section: Discussionsupporting
confidence: 82%
“…To determine if the susceptibility of individuals with diabetes is the result of lower titers or a poor protective ability of generated antibodies to capsular polysaccharide and/or protein antigens, we measured both titers and protective antibody functions. Our observation that diabetes was associated with poor antibody responses to PspA was consistent with observations made by Nam et al indicating that baseline positive rates of cross-reactive antibodies against pandemic influenza virus in patients with diabetes were lower than those in age-and sex-matched nondiabetes controls (35). Additionally, Fabrizi et al reported a lower seroprotection rate elicited by the hepatitis B vaccine in diabetics (both influenza virus and hepatitis B virus are protein antigens) (13).…”
Section: Discussionsupporting
confidence: 81%
“…To our knowledge, only seven studies have been published regarding the immunogenicity of influenza vaccination among diabetic patients (6)(7)(8)(9)(10)(11)(12). Of them, six studies concluded that the immune response was similar between diabetic individuals and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that diabetic individuals have an immune response to influenza vaccination similar to that of healthy controls, while a few studies have reported suboptimal responses in diabetic subjects (6)(7)(8)(9)(10)(11)(12). Immunogenicity should be maintained throughout the entire seasonal epidemic; therefore, an evaluation of longterm immunogenicity is essential before the current conventional vaccination program can be recommended.…”
mentioning
confidence: 99%